Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1016/0168-8278(95)80218-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications in living related liver transplantation detected with intraoperative and postoperative Doppler US

Abstract: Serial intra- and post-operative Doppler US was a useful technique for making an early diagnosis of abnormal hemodynamics of the graft circulation. Furthermore, intraoperative Doppler US could assess reconstructed vessels objectively and would reduce the incidence of vascular complications following transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 26 publications
2
51
0
2
Order By: Relevance
“…It has been demonstrated that the portal venous size and flow velocity correlated directly with the portal flow volume. In our experience, the mean velocity of the portal flow was 38.63 f 8.31 cm/s and the portal blood flow volume per body weight was 22.54 f 8.27 ml/min per kg in non-complicated vascular patients, with 9 ml/min per kg being defined as the lowest limit of acceptable portal flow volume during and after transplantation [5,15]. In cases where low portal inflow is associated with suspected portal hypertension syndrome, angiographic hemodynamic confirmation or indirect pressure gradient measurement (hepatic wedge and splenic direct pulp pressure) is indicated [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the portal venous size and flow velocity correlated directly with the portal flow volume. In our experience, the mean velocity of the portal flow was 38.63 f 8.31 cm/s and the portal blood flow volume per body weight was 22.54 f 8.27 ml/min per kg in non-complicated vascular patients, with 9 ml/min per kg being defined as the lowest limit of acceptable portal flow volume during and after transplantation [5,15]. In cases where low portal inflow is associated with suspected portal hypertension syndrome, angiographic hemodynamic confirmation or indirect pressure gradient measurement (hepatic wedge and splenic direct pulp pressure) is indicated [13].…”
Section: Discussionmentioning
confidence: 99%
“…Reported incidences of hepatic venous outflow occlusion following LDLT range from 3.9% to 16.6%. 3,[15][16][17] In LDLT recipients, early posttransplant hepatic venous occlusion may induce liver function deterioration, graft failure, or death because of the graft's size insufficiency. 1,18 Thus, early adequate treatment of hepatic venous outflow occlusion is important for good graft function.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler ultrasonography has been used with humans as a noninvasive technique for real time diagnoses of aberrant blood flow (Someda et al, 1995;Whelan and Barry, 1992), stenosis (Hatle et al, 1980;Olin et al, 1995;Schmidt et al, 1997), and occlusions (Moneta et al, 1992;Müller et al, 1995). It also has been used to determine vasoconstrictive and blood flow responses in cattle (Aiken et al, 2007; and sheep (Aiken et al, 2011) to ergot alkaloids, and was performed with steers to quantify artery lumen area and blood flow responses to heat and cold challenges (Kirch et al, 2008).…”
Section: Wwwintechopencommentioning
confidence: 99%